Why Teach Alternative Dispute Resolution to Law Students? Part One: Past and Current Practices and Some Unanswered Questions - Judy Gutman; Tom Fisher; Erika Martens (Legal Education Review)
The revolution in media and global communications in the last few decades has transformed the very basic foundations of knowledge and education. The pedagogical literature has been advocating for the development of media literacy across the curriculum. However, in Canada the Law School classroom, with its teaching philosophy built during an exclusively print-centred era, has not yet opened its doors to audiovisual teaching methodologies or to media literacy. The article describes some student-centred activities that are informed by visual pedagogy. Approaching the teaching of criminal law from the visual pedagogy perspective helps students develop media literacy, which enables a level of interactivity and critical thinking not achieved with traditional teaching methods.